If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11r + -2 + (-2r) + -1(-5w) = 0 Remove parenthesis around (-5w) 11r + -2 + (-2r) + -1 * -5w = 0 Multiply -1 * -5 11r + -2 + (-2r) + 5w = 0 Reorder the terms: -2 + 11r + (-2r) + 5w = 0 Combine like terms: 11r + (-2r) = 9r -2 + 9r + 5w = 0 Solving -2 + 9r + 5w = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 9r + 2 + 5w = 0 + 2 Reorder the terms: -2 + 2 + 9r + 5w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 9r + 5w = 0 + 2 9r + 5w = 0 + 2 Combine like terms: 0 + 2 = 2 9r + 5w = 2 Add '-5w' to each side of the equation. 9r + 5w + -5w = 2 + -5w Combine like terms: 5w + -5w = 0 9r + 0 = 2 + -5w 9r = 2 + -5w Divide each side by '9'. r = 0.2222222222 + -0.5555555556w Simplifying r = 0.2222222222 + -0.5555555556w
| 18+17x^2-36x=0 | | 5+a-(-5b)= | | 18+19x^2-36x=0 | | (W-5)(w-5)-8=0 | | m+4m+r+3m= | | 200+6m=500-5m | | z/2-7=12 | | 0.1x+0.2x+x=1397250 | | (0.1x)(0.2x)(x)=1397250 | | 20x-6-18x+2=17x-8-15x+16 | | 10y/2=120 | | 3(24)+72=6(24) | | -3y(3y+4)=4 | | x^4+x^2+2x^2+4=2x^2+12 | | 5x+70=2x+130 | | 2x^2dy-(x^2+y^2)dx=0 | | -2x=5-5y | | 23-2m=19 | | x(4x-11)=(x+1)(x-3) | | ¹16/9=3 | | 12x-3(2x-3)=9+6x | | 22x-4(3x-6)=24+10x | | (y-15)=-12/17 | | 29/3 | | 11x-2(3x-5)=14+5x | | 89/9 | | 4x-5(x+1)=7 | | 16x-2(3x-3)=8+10x | | .5y=3x-1 | | -10x-3=-5(2x+8)+37 | | 3w+4w-3=32 | | -6x-2=-3(2x+8)+22 |